Demonstration of the ability of the bacterial polysaccharide FucoPol to flocculate kaolin suspensions. Issue 3 (28th January 2020) - Araújo, Diana; Concórdio-Reis, Patrícia; Marques, Ana C.; Sevrin, Chantal; Grandfils, Christian; Alves, Vítor D.; Fortunato, Elvira; Reis, Maria A. M.; Freitas, Filomena
ABSTRACT: In this study, the flocculation properties of FucoPol, a bacterial extracellular polysaccharide, were investigated. FucoPol is a high molecular weight polymer and negatively charged due to the presence of glucuronic acid and the acyl groups succinyl and pyruvyl. High flocculation rate values (>70%) were achieved with a low bioflocculant dosage of 1 mg/L, for pH values in the range 3–5 and temperature within 15–20°C. The bioflocculant was also shown to be stable after freezing/thawing and heating up to 100°C. Given the polymer's anionic character, the size of flocs formed and their surface profile, bridging seems to be the main flocculation mechanism of FucoPol. This study demonstrated that FucoPol is a promising natural, biodegradable and biocompatible alternative to the currently used synthetic or inorganic hazardous products, with potential to be used as a novel flocculation agent in several applications, such as water treatment, food or mining. Further studies will involve evaluating the reduction of cation dosage on flocculation efficiency, as well as testing the applicability of FucoPol to flocculate different types of suspended solids, such as, for example, activated carbons, soil solids or yeast cells. GRAPHICAL ABSTRACT: